Framework Proposal for Environmental Impacts Assessment (EIA) of Nuclear Activities and their Role in Achieving Sustainable Development (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The importance of preparing a study to assess the environmental impacts of nuclear and radiological activities to confirm its commitment to local and international requirements and standards for the practice of these activities, to identify and analyze sensitive components of the current environment, to determine the type, nature and importance of potential environmental impacts during construction, operation, accidents and emergency conditions, and to identify practical and feasible mitigation measures and recommend them to reduce of the environmental impacts, if any, and setting a general framework for the environmental management plan and the environmental monitoring plan for the facility in order to ensure that all parties concerned and affected by the activities under evaluation are taken into consideration, and the research aims to prepare a model for the steps for preparing an environmental impact assessment by proactive approach commensurate with very specific nature of nuclear and radiological activities. And to contribute to achieving sustainable development for those activities.